Suicides by opium and its derivatives, in England and Wales, 1850-1950. - Clarke, M (1985)
In the mid-nineteenth century opium and its derivatives, such as laudanum and morphine, were the most common poisons in suicides in England and Wales. With legislative restrictions on these 'dangerous drugs' such a use declined. This study attempts to show this trend and indicates the large variety of these opium-related suicides.